Designing the Golden Calf: Pens and Presumption in the Production of a "Divine" Image. - VanDyke, Elizabeth (Journal of Biblical Literature, 2022)
This article reexamines the creation of the golden calf in Exod 32:4a. Though the text in question is brief, it has been a puzzle to translators and commentators since the time of the LXX and warrants reassessment in light of new inscriptional and linguistic data. Syntactical analysis and comparative Semitics show that Aaron not only produced the calf but designed it as well. This interpretation requires glossing the verb in the passage, , according to its cognates in Akkadian and Aramaic as "to draw" or "to design." The resulting translation solves the grammatical difficulties of the text and fits a greater cultural concern for the "divine design" of cultic objects. I will also suggest that the implement Aaron used to design the calf was not an engraving tool but a rush pen. Artifacts from Egypt as well as from Kuntillet 'Ajrud evidence how ancient scribes sketched, played with, and practiced their craft with ink and pen before creating a final product. Understanding the tool in this manner also suits its usage in Isa 8:1 as a writing instrument used on a large piece of papyrus. In sum, the translation "and he designed it with a rush pen and made it into a cast-metal calf" solves the grammatical and lexical difficulties of the passage while adding to our understanding of Exodus's overall polemic against the bovine image.